52 year old Filipino female with decreased vision OD for two weeks - Ai, Everett; Amin, Haris I. (Digital Journal of Ophthalmology, 1998)
52 year old Filipino female presented on 9/97 with decreased vision OD for two weeks. She had been diagnosed with central serous retinopathy in 9/83 (age 38) when a retinal pigment epithelial detachment was noted OD. This had not resolved by 6/84 and was treated with laser photocoagulation with good efficacy (acuity improved from 20/40 to 20/15 in one month). She next presented in 2/92 with 20/50 OD and was diagnosed with age related macular degeneration. She was thought to have subretinal neovascularization and was treated with laser photocoagulation. Vision had improved to 20/20 in 7/92.